Pentingnya Penggunaan Sistem Informasi Manajemen Rumah Sakit Generik Open Source (SIMRS GOS) dalam Meningkatkan Mutu Pelayanan Rumah Sakit - Fefni Kaldian (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
Quality of health care in hospitals is determined by many factors. In measuring the quality, it can be seen from various dimensions. One of them concerns on the reliability of which is the ability provide services immediately, precisely (accurately) and satisfyingly. To provide services fast, precisely (accurately) and satisfyingly is by implementing a web-based information system called Hospital Information Management System of Generic Open Source (SIMRS GOS). SIMRS GOS is one program from the Ministry of Health of Indonesia that must be applied by all hospitals in changing for the better service system. Implementation of the management and development SIMRS should be able to improve and support the health care process in hospitals, includes the speed, accuracy, integration, enhanced customer service, increased efficiency, and ease of reporting in operational execution.